2019
DOI: 10.1111/ldrp.12210
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Alignment of Mathematics Instructional Practices and Mathematics Vocabulary between Core and Intervention Materials

Abstract: Within a multitiered system of support (MTSS), students who struggle to learn mathematics often receive core instruction and supplemental intervention in different settings, with different teachers and different sets of curriculum materials, all of which can result in poor alignment. This curriculum crosswalk describes how three sets of materials commonly used to provide core instruction and intervention differ with regard to mathematics practices and vocabulary. The results indicate that there is little overl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…When considering the importance of fidelity, many teachers and interventionists may fill the role of curriculum transmitters (Shawer, 2010), while making small adaptations to the curriculum to meet some individual needs of students. For example, teachers may start each lesson with a short game that pre-teaches vocabulary for that lesson, coordinate vocabulary terms and instruction across classroom and intervention settings (i.e., with general education teachers who teach regular mathematics class), and create more opportunities within the lesson for students to communicate about mathematics (Nelson et al, 2020). Finally, teachers may want to consider monitoring student understanding of mathematics vocabulary terms through formative assessment (e.g., exit tickets).…”
Section: Implications For Practicementioning
confidence: 99%
“…When considering the importance of fidelity, many teachers and interventionists may fill the role of curriculum transmitters (Shawer, 2010), while making small adaptations to the curriculum to meet some individual needs of students. For example, teachers may start each lesson with a short game that pre-teaches vocabulary for that lesson, coordinate vocabulary terms and instruction across classroom and intervention settings (i.e., with general education teachers who teach regular mathematics class), and create more opportunities within the lesson for students to communicate about mathematics (Nelson et al, 2020). Finally, teachers may want to consider monitoring student understanding of mathematics vocabulary terms through formative assessment (e.g., exit tickets).…”
Section: Implications For Practicementioning
confidence: 99%
“…Second, we did not utilize a BAU control condition to compare the effects of our mathematics intervention to general core instruction. Researchers have reported on the misalignment between tiers, including the misalignment of mathematics vocabulary between tiers (Nelson et al., 2020), and practitioners will benefit from future research that examines how mathematics vocabulary interventions supplement and align with core mathematics instruction. Third, because students were also participating in district‐, school‐, and classroom‐based screening and progress monitoring assessments, we made a conscious decision to avoid additional testing beyond what we deemed necessary for a small pilot study.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…When intensive intervention leans heavily on explicit instruction or direct instruction components (Nelson et al., 2019) alone, therefore, there is little room for building the language of mathematics, leaving students receiving interventions without the skills to join their peers in mathematical discourse (or numbers talks) when receiving universal/core instruction. This lack of opportunity is further compounded for children who represent intersectional identities, that is, students with MD who also are ELs and need additional language support.…”
mentioning
confidence: 99%
“…Typically, many tiered intervention programs are explicit in nature, meaning they are scripted and often teacher‐directed (i.e., more direct instruction than explicit and systematic instruction). Many standardized programs include the tenets of explicit instruction, which begin with modeling, move to guided practice, and then move to independent practice (Archer & Hughes, 2011), often without a focus on language or mathematics vocabulary (Nelson et al., 2019). But while research has shown that this is an effective instructional strategy for EL students with MD, it often does not include skill instruction that leads to increased discourse in core mathematical instruction (Griffin et al., 2013).…”
mentioning
confidence: 99%